Application of Genomics in Supporting Efficient Conservation and Utilization of Plant Genetic Resources - Wambugu, P.W.; Ndjiondjop, M.N.; Rangan, P.; Henry, R. J. (2024)
Many gene banks have adopted various genomic tools and have integrated them into their routine genebank operations. In this chapter, we review the actual and potential applications of genomics in advancing seed bank-based ex situ conservation and utilization of plant genetic resources. Genomic tools are supporting germplasm acquisition efforts through conservation gap analysis and enabling the identification of rare, threatened, and novel genetic resources that need to be prioritized for conservation. Analysis of germplasm from different environments using transcriptomic approaches assists in identifying the candidate genes associated with desirable traits and biologically important pathways. Identification of genetic redundancy is enabling collection rationalization thus enhancing cost efficiency in plant genetic resources conservation. Genomics is providing greater capacity on developing core collections and trait-specific subsets thus promoting utilization of plant genetic resource collections. Emerging genomic technologies are providing capacity to support in situ conservation and biodiversity restoration using ex situ conserved diversity. Analysis of genome environment associations is enabling the identification of germplasm that potentially possesses the necessary adaptive capacity and desired traits. The lack of a standardized approach on documenting and sharing big genomic data being generated from ex situ collections however remains a major challenge in enhancing genomics-assisted conservation.